Quality of life at work and Burnout in family health strategy workers - Marta Maria Souza Borges; Viviane Reis Nunes; Mateus Portilho Pires; Bianca Guimarães Lima; Ulisses Vilela Hipólito; Mirian Cristina dos Santos Almeida (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To analyze the correlation between quality of life at work and Burnout in workers in the Family Health Strategy. Methods: Correlational, cross-sectional study carried out with 112 workers, in the pandemic period (October/2020 to June/2021), in Palmas/Tocantins. The Quality of Work Life Assessment Questionnaire (QWLQ-bref) and the Maslach Burnout Inventory - Human Services Survey (MBI-HSS) were used. Results: A strong negative correlation was identified between Emotional Exhaustion and the Physical/Health, Professional and Total Quality of Life Score at work; and moderate negative correlation between Depersonalization and all domains of Quality of Work Life. Professional Achievement showed a moderate positive correlation with the Psychological and Personal domains and with the Total Quality of Work Life Score. Conclusion: The best Quality of Work Life indices were correlated with lower Emotional Exhaustion and Depersonalization scores and higher scores of Professional Achievement.